Demorgans Theorem and Boolean Functions
Demorgans Theorem and Boolean Functions
December 6, 2022 1
Consensus Theorem
1. xy + x’z + yz = xy + x’z
2. (x+y)•(x’+z)•(y+z) = (x+y)•(x’+z) -- (dual)
Proof:
xy + x’z + yz = xy + x’z + (x+x’)yz
= xy + x’z + xyz + x’yz
= (xy + xyz) + (x’z + x’zy)
= xy + x’z
QED (2 true by duality).
December 6, 2022 2
Operator Precedence
The operator precedence for evaluating Boolean
Expression is
Parentheses
NOT
AND
OR
Examples
x y' + z
(x y + z)'
December 6, 2022 3
Boolean Functions
A Boolean function
Binary variables
Binary operators OR and AND
Unary operator NOT
Parentheses
Examples
F1= x y z'
F2 = x + y'z
F3 = x' y' z + x' y z + x y'
F4 = x y' + x' z
December 6, 2022 4
Boolean Functions
The truth table of 2n entries
x y z F1 F2 F3 F4
0 0 0 0 0 0 0
0 0 1 0 1 1 1
0 1 0 0 0 0 0
0 1 1 0 0 1 1
1 0 0 0 1 1 1
1 0 1 0 1 1 1
1 1 0 1 1 0 0
1 1 1 0 1 0 0
Two Boolean expressions may specify the same function
F3 = F4
December 6, 2022 5
Boolean Functions
Implementation with logic gates
F4 is more economical
F2 = x + y'z
F4 = x y' + x' z
December 6, 2022 6
Algebraic Manipulation
To minimize Boolean expressions
Literal: a primed or unprimed variable (an input to a gate)
Term: an implementation with a gate
The minimization of the number of literals and the number of
terms → a circuit with less equipment
It is a hard problem (no specific rules to follow)
Example 2.1
1. x(x'+y) = xx' + xy = 0+xy = xy
2. x+x'y = (x+x')(x+y) = 1 (x+y) = x+y
3. (x+y)(x+y') = x+xy+xy'+yy' = x(1+y+y') = x
4. xy + x'z + yz = xy + x'z + yz(x+x') = xy + x'z + yzx + yzx' =
xy(1+z) + x'z(1+y) = xy +x'z
5. (x+y)(x'+z)(y+z) = (x+y)(x'+z), by duality from function 4.
(consensus theorem with duality)
December 6, 2022 7
Complement of a Function
An interchange of 0's for 1's and 1's for 0's in the value
of F
By DeMorgan's theorem
(A+B+C)' = (A+X)' let B+C = X
= A'X' by theorem 5(a) (DeMorgan's)
= A'(B+C)' substitute B+C = X
= A'(B'C') by theorem 5(a) (DeMorgan's)
= A'B'C' by theorem 4(b) (associative)
Generalizations: a function is obtained by interchanging
AND and OR operators and complementing each literal.
(A+B+C+D+ ... +F)' = A'B'C'D'... F'
(ABCD ... F)' = A'+ B'+C'+D' ... +F'
December 6, 2022 8
Examples
Example 2.2
F1' = (x'yz' + x'y'z)' = (x'yz')' (x'y'z)' = (x+y'+z) (x+y+z')
F2' = [x(y'z'+yz)]' = x' + (y'z'+yz)' = x' + (y'z')' (yz)‘
= x' + (y+z) (y'+z')
= x' + yz‘+y'z
Example 2.3: a simpler procedure
Take the dual of the function and complement each literal
1. F1 = x'yz' + x'y'z.
The dual of F1 is (x'+y+z') (x'+y'+z).
Complement each literal: (x+y'+z)(x+y+z') = F1'
2. F2 = x(y' z' + yz).
The dual of F2 is x+(y'+z') (y+z).
Complement each literal: x'+(y+z)(y' +z') = F2'
December 6, 2022 9